The Book of Fate - Meltzer, Brad (London Hodder and Stoughton Ltd., 2006)
Six minutes from now, one of us would be dead. None of us knew it was coming. So says Wes Holloway, a young presidential aide, about the day he put Ron Boyle, the chief executive's oldest friend, into the presidents limousine. By the trips end, a crazed assassin would permanently disfigure Wes a kill Boyle. Now, eight years later, Boyle has been spotted alive. Trying to figure out what really happened takes Wes back into disturbing secrets buried in Freemason history, a decade-old presidential crossword puzzle, and a two-hundred-year old code invented by Thomas Jefferson that conceals secrets worth dying for.
English Fiction.
Keywords: Political fiction -- Washington (D.C.) -- United States